The Influence Of Work Motivation And Compensation On Employee Performance At Pt Pantjatunggal Knitting Mill Branch Of Mpu Tantular Semarang - Lailatunnisak - Amanu; Karnowahadi - Karnowahadi; Rara Ririnbudi Utaminingsih (Politeknik Negeri Semarang, 2020)
Based on the research background,, the problem in this research is the sewing department never reached the production target in 2018. The purposes of this research are to find out influence of work motivation on employee performance at PT Pantjatunggal Knitting Mill branch of Mpu Tantular Semarang, compensation on employee performance at PT Pantjatunggal Knitting Mill branch of Mpu Tantular Semarang, and work motivation and compensation on employee performance at PT Pantjatunggal Knitting Mill branch of Mpu Tantular Semarang. Data collection used are questionnaires, interview, and literature review. The sample in this study are 80 employees of the sewing devison at PT Pantjatunggal Knitting Mill branch of Mpu Tantular Semarang. The data analysis technique used is multiple regression. From the analysis of multiple regression in this research, could be found that the work motivation and compensation influence employee performance. The most dominant variable that influence the employee performance is the work motivation. While from the result of determination coefficient (Adjusted R Square) shows that 0,319 or 31,9% of the independent variable are work motivation and compensation. It means that 31,9% of the employee performance is explained by work motivation and compensation. While 68,1% wis explained by other factors not examined in this research.